2019
DOI: 10.1108/afr-07-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

State-space approach to capital return in nonlinear growth processes

Abstract: Structured Abstract PurposeWe introduce a capital return rate function for growth processes, and apply it to financial sustainability considerations in growing multiannual plants. DesignA partition function of change rate of capitalization is introduced, as well as that of capitalization itself, and the expected value of capital return rate is produced as the ratio of the two functions. FindingsFinancial sustainability significantly differs from maximum-yield sustainability, and does not depend on any external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…It has been recently shown that Eq. (7) corresponds to the ratio of the partition functions of change rate of capitalization and capitalization itself [19]. It also has been recently shown that maximization of net present value of future revenues may result in financially devastating consequences [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently shown that Eq. (7) corresponds to the ratio of the partition functions of change rate of capitalization and capitalization itself [19]. It also has been recently shown that maximization of net present value of future revenues may result in financially devastating consequences [20].…”
Section: Methodsmentioning
confidence: 99%
“…(2) was introduced in 1860 [24]; an expected value was mentioned in 1967 [25,26], however applications have been introduced only recently [19,20,13,14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the constancy of the expected value of capital return rate in time requires that prices and expenses do not evolve in real terms. Then, the expected value of the capital return rate becomes It has been recently shown that Equation (7) corresponds to the ratio of the partition functions of the change rate of capitalization and capitalization itself [29]. It also has been recently shown that the maximization of the net present value of future revenues may result in financially devastating consequences [30].…”
Section: Financial Considerationsmentioning
confidence: 99%
“…The feasibility of harvesting is investigated in five-year intervals, always considering two options: thinning or clearcut. Clearcutting expenses are lower than thinning harvesting costs, according to Parkatti et al [33], stated to be based on a productivity study of Nurminen et al In addition to high thinnings intended to maximize capital return rate [21,22,29,30,23], the consequences of following semi-official silvicultural guidance commonly applied in the area [35] are discussed. Thinnings are predominantly applied from below, and any rotation is It has been recently shown that policies based on carbon rent are equivalent to policies based on carbon sequestration subsidies and taxies [18].…”
Section: Financial Considerationsmentioning
confidence: 99%